Hired minds a career guide for engineering students and graduates ryan Gardner - Gardner, Bryan (American Institute of Aeronautics and Astronautics, 2007)
This not your standard book on how to write a resume or interview. Written in an up-beat, entertaining style, Gardner uses the personal experiences of over two dozen beginning engineers to illustrate the different paths for developing engineering experience as an undergrad, landing the job you want, and starting off right as an engineer. He gives tips on resume writing and interviewing skills, getting through the first confusing days on the job, how to create excitement from the mundane tasks, seeking out the interesting work, balancing work and school, and even engineering your finances once you're on the job. Hired Minds covers the office, team, and personal work dynamics that are essential to successful engineering, especially during the first year. The book is designed to accompany university senior design project courses, helping to successfully bridge the transition from education to industry.